Paper 5: Historic Mortars from the Coudenberg Archaeological Site: Characterization and Source of Raw Materials. (February 2014) - Fontaine, Laurent; Hayen, Roald; Godts, Sebastiaan; De Clercq, Hilde
<x content-type="archive" xml:space="preserve">Abstract</x> The characterization of historic mortars by means of a concise methodology of material analyses can provide crucial information with regard to the origin of the raw materials and the ancient mortar technology. For the analysis of the historic mortars of the Coudenberg archaeological site, the methodology consists of optical and scanning electron microscopy, simultaneous thermal analysis, and an acidic treatment. These analyses were carried out on a total of seventeen samples lifted from various areas in the site, in function of the building chronology resulting from a historic built investigation. The type of binder and aggregate as well as their volumetric ratio were determined. Both binder and aggregate present distinctive features, which made it possible to identify the probable geological provenance of the raw materials. The observations are verified with available historical records regarding the construction of the main banqueting hall — the Aula Magna — and the use of raw materials such as limestone and sand for the production of lime and construction purposes.